Hubungan Dukungan Suami Terhadap Tingkat Kecemasan Ibu Hamil Primigravida Trimester III Menghadapi Persalinan di Puskesmas Benu-Benua Kendari Barat - Yulli Fety Fety (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
pregnant women did not receive the support of their husbands. Whereas 1 primigravida pregnant woman was stated to have received support from her husband both in terms of emotional support, assessment, instrumental and information. This study aims to determine the relationship of the husband's support to the level of anxiety of third trimester primigravida pregnant women in the working area of the Benu-Benua Kendari West Health Center. This type of research is a quantitative study with a